A Model for Assessing the Service Quality of University Library Websites. (6th June 2013) - Wu, Chung-Min; Hsieh, Ching-Lin; Chang, Kuei-Lun
Abstract : Evaluating the e-service quality is essential to organizations. The future of e-libraries has a vital place in universities. Libraries need to use websites as means to provide access to information resources, news and events. The importance of assessing e-service quality of libraries is significant. Previous researchers have developed many methods for assessing e-service quality. However, most of them only focus on the independent hierarchical structure. In this paper, we would like to figure out the criteria for assessing the service quality of library websites from university students' viewpoints. According to interdependent criteria, the analytic network process (ANP) approach is employed to (i) generate the priority weights of each criterion; (ii) measure the service quality of university library websites. 12 web-based service criteria are identified according to 3144 university students' viewpoints based on fuzzy Delphi method. On the basis of past studies, we divide 12 criteria into 3 perspectives, namely, system, efficiency, and information quality to measure the service quality of university library websites. On the basis of 3 perspectives and 12 important criteria, service quality of university library websites could be measured more effectively. Moreover, the practical application to measure the service quality of the old and new versions of one university library website presented in Section 5 is generic and also suitable to be exploited for Taiwanese universities.